(3Yde GdELJeGYs (3GdfXQjI hGdefgLs - (3JTjQJhf, ejds; (3GdLhgQj, gfGAs; (3HQGhf, Bfs ((3GdbGgQIs (3GdeQcR Gdbhej ddJQLeIs, 2012)
(3gPG GdcJGH jYQV GMJjGLGJ GdOGQS GdeHJOF dYde GdELJeGY hjMQU GdcJGH Ydi GdEMGWI GdhGajI Hcd GdCacGQ, hGdbVGjG hGdefgLjGJ GdJbdjOjI, hjhVM HCeKdI hJOQjHGJ JWHjbjI GSJLGHI YdeGA GdELJeGY dcd GdeSJLOGJ GdfXQjI hGdefgLjI, NGUI eG LdHJg CacGQ eG HYO GdMOGKI ef JLOjOGJs
(3GdcJGH jTJed Ydi eYLe eUWdMGJ EfLdjRj (B- (3YQHjs
(3gPG GdcJGH JQLeI dcJGH (BTheory & Churtons
11
Keywords: (3GdELJeGYs -- (3Ydes; (3Yde GdELJeGYs